Use of Interorganisational Systems: An Empirical Analysis - Mirko Hoppe; Hans-Joachim Schramm (Technische Universität Dresden, Fakultät Verkehrswissenschaften, 2004)
Electronic linkages between organisations enabled by interorganisational information systems (IOS) such as Electronic Data Interchange (EDI), Internet- based applications or cargo community systems are becoming increasingly important. Recently, many studies have examined the impact of electronic integration in logistics chains. However, there is a need to examine which factors on the perceived level of an interorganisational partnership are important for the management of information systems. We extend further the information processing model based on Galbraith [1] and Bensaou and Venkatraman [2] in a logistics network context. Their theoretical concept gives some explanations about a fit between information processing requirements, as determined in partnership design, and the information processing capabilities realised in information systems. This was further explored conducting a survey amongst German network organisations of freight forwarders in groupage service or contract logistics as a starting point because of their common usage of different interorganisational information systems. Surprisingly, our study shows only a slight influence of interorganisational tasks on the management of information systems. Moreover, our findings suggest that employment of IOS across firms observed is limited by structural factors (i.e. asset specificity) and nature of interorganisational relationship (i.e. trust, power). These factors are positively associated with satisfaction about information systems usage and performance.
Keywords: 330; interorganisational information systems; information processing model; co-operation; logistics networks; freight forwarder networks; Logistikunternehmen; Business Network; Logistik-Informationssystem; Unternehmenskooperation; Spedition; Organisationsstruktur; Deutschland